A new Graphical User Interface for the CONTSID toolbox for Matlab. Issue 7 (2021) - Garnier, H.; Gilson, M.; Muller, H.; Chen, F.
Abstract: The main purpose of this contribution is to describe the new features of the latest version 7.4 of the CONtinuous-Time System IDentification (CONTSID) toolbox for Matlab. The main addition is a new Graphical User Interface (GUI), which allows the user in a friendly and easy way to perform data analysis, model parameter estimation as well as model validation. The recent additions for MISO time-delay transfer function model identification are also briefly introduced.